Youth sport 2.0? The development of eSports in Norway from 2016 to 2019 - Tjønndal, A.; Skauge, M. (Qualitative Research in Sport, Exercise and Health, 2021)
Digital technology has deeply impacted the ways in which youth play and consume sport as part of their leisure activities. Central to this topic is the rise of new virtually played sports: eSports. eSports has taken the global youth sportscape by storm - so much so that the International Olympic Committee (IOC) are looking to capitalise on its popularity as part of the organisation`s work to make the Olympic Games more attractive to youth. The aim of the current study is to explore the development and expansion of eSports in Norway from 2016 to 2019. This is done through a qualitative content analysis of 102 media texts. The findings reveal a tendency towards eSports gradually being integrated in the Norwegian sports model by local sports clubs. Our material also reveals a shifting trend towards acceptance of eSports as `real` sports. This is particularly evident through the introduction of eSports in the school system and eSerien - a national professional FIFA league organised by the Norwegian Football Federation (NFF). Furthermore, the texts included in the sample also illustrates how some groups of people express resistance towards the growth of eSports in Norway.